A Superlattice-Stabilized Layered CuS Anode for High-Performance Aqueous Zinc-Ion Batteries - Zhang, Jiaqian; Lei, Qi; Ren, Zhiguo; Zhu, Xiaohui; Li, Ji; Li, Zhao; Liu, Shilei; Ding, Yiran; Jiang, Zheng; Li, Jiong; Huang, Yaobo; Li, Xiaolong; et al. (ACS nano, 2021)
Rechargeable aqueous zinc ion batteries (AZIBs) are attracting extensive attention owing to environmental friendliness and high safety. However, its practical applications are limited to the poor Coulombic efficiency and stability of a Zn anode. Herein, we demonstrate a periodically stacked CuS-CTAB superlattice, as a competitive conversion-type anode for AZIBs with greatly improved specific capacity, rate performance, and stability. The CuS layers react with Zn2+ to endow high capacity, while CTAB layers serve to stabilize the structure and facilitate Zn2+ diffusion kinetics. Accordingly, CuS-CTAB shows superior rate performance (225.3 mA h g–1 at 0.1 A g–1 with 144.4 mA h g–1 at 10 A g–1) and a respectable cyclability of 87.6% capacity retention over 3400 cycles at 10 A g–1. In view of the outstanding electrochemical properties, full batteries constructed with a CuS-CTAB anode and cathode (Zn x FeCo(CN)6 and Zn x MnO2) are evaluated in coin cells, which demonstrate impressive full-battery performance.